Dual specificity phosphatase 6 deficiency is associated with impaired systemic glucose tolerance and reversible weight retardation in mice. - Katrin Pfuhlmann; Paul T Pfluger; Sonja C Schriever; Timo D Müller; Matthias H Tschöp; Kerstin Stemmer (PLoS ONE)
Here, we aimed to investigate the potential role of DUSP6, a dual specificity phosphatase, that specifically inactivates extracellular signal-regulated kinase (ERK), for the regulation of body weight and glucose homeostasis. We further assessed whether metabolic challenges affect Dusp6 expression in selected brain areas or white adipose tissue. Hypothalamic Dusp6 mRNA levels remained unchanged in chow-fed lean vs. high fat diet (HFD) fed obese C57Bl/6J mice, and in C57Bl/6J mice undergoing prolonged fasting or refeeding with fat free diet (FFD) or HFD. Similarly, Dusp6 expression levels were unchanged in selected brain regions of Lepob mice treated with 1 mg/kg of leptin for 6 days, compared to pair-fed or saline-treated Lepob controls. Dusp6 expression levels remained unaltered in vitro in primary adipocytes undergoing differentiation, but were increased in eWAT of HFD-fed obese C57Bl/6J mice, compared to chow-fed lean controls. Global chow-fed DUSP6 KO mice displayed reduced body weight and lean mass and slightly increased fat mass at a young age, which is indicative for early-age weight retardation. Subsequent exposure to HFD led to a significant increase in lean mass and body weight in DUSP6 deficient mice, compared to WT controls. Nevertheless, after 26 weeks of high-fat diet exposure, we observed comparable body weight, fat and lean mass in DUSP6 WT and KO mice, suggesting overall normal susceptibility to develop obesity. In line with the increased weight gain to compensate for early-age weight retardation, HFD-fed DUSP6 KO displayed increased expression levels of anabolic genes involved in lipid and cholesterol metabolism in the epididymal white adipose tissue (eWAT), compared to WT controls. Glucose tolerance was perturbed in both chow-fed lean or HFD-fed obese DUSP6 KO, compared to their respective WT controls. Overall, our data indicate that DUSP6 deficiency has limited impact on the regulation of energy metabolism, but impairs systemic glucose tolerance. Our data are in conflict to earlier reports that propose protection from diet-induced obesity and glucose intolerance in DUSP6 deficient mice. Reasons for the discrepancies remain elusive, but may entail differential genetic backgrounds, environmental factors such as the type and source of HFD, or alterations in the gut microbiome between facilities.